National campaigns for charitable causes: exploring the Portuguese case - Simaens, A.; Abreu, M. E.; Felgueiras, Ana (XV Congreso de Investigadores en Economía Social de CIRIEC, 2014)
Individual donations constitute an important source of income for nonprofit organizations (NPOs) and most engage in fundraising activities to mobilize individuals’ monetary contributions to advance their social mission, including national campaigns for charitable causes. Scholars from different disciplinary backgrounds have been interested in explaining general drivers of individual donations (e.g. Bennett and Kottasz 2000; Bekkers and Schuyt 2008; Bekkers and Wiepking 2011; Wiepking and Bekkers 2012). What is more, a new dimension of global charity is recognized as a new trend of nowadays cultures, along with other international stages (Rivera, 2008). No academic studies have addressed the issue of national campaigns for charitable causes in Portugal. This paper contributes to fill in the identified literature research gap by presenting findings from an exploratory quantitative and qualitative analysis of seventeen national campaigns, the NPOs promoting them, and the donors as they are perceived by the promoter NPOs, from 2003 to 2012. Results show the success in quantitative terms of the national campaigns implemented by Portuguese Cáritas; donors’ preference for high-profile media coverage appeals, high expected social impact, and campaigns with a short duration; and the importance of indicators other than the amounts raised to assess the success of national campaigns for charitable causes.